Are habitat changes driving protist community shifts? A case study in Daya Bay, China. (31st October 2019) - Qin, Chuanxin; Zhu, Wentao; Ma, Hongmei; Duan, Dingyu; Zuo, Tao; Xi, Shigai; Pan, Wanni
Abstract: Protists play an important role in regulating marine ecosystems, and their diversity and community structure differ both temporally and spatially. Little research has been conducted on the structure and function of protists associated with coral reefs and artificial reefs, which are important and unique habitats for marine life. In this study, based on Illumina sequencing analysis of 18S rDNA, the diversity and community structure of protists in coral reef, artificial reef and open-water areas in Daya Bay were described for the first time. The biodiversity of protists in open-water areas was higher than that in artificial reefs and slightly higher than that in coral reefs, but there were no significant differences in protist alpha diversity among the different habitats or depths in Daya Bay. The depth of Daya Bay was not sufficient to significantly affect the distribution of the protist communities, while pH and salinity had the strongest impacts. Furthermore, the correlations between protist abundance and environmental variables of the water mass were much weaker than those between habitat and protist abundance. PERMANOVA revealed significant differences in protist diversity among the habitats. The interactions of living organisms and differences among habitats play key roles in the formation of protist communities, and artificial reefs were found to change the community structure of protists, suggesting that artificial reefs play a role similar to that of coral reefs to improve ecological functions and restore ecosystems.